Challenges Associated with Generating Reliable Nanogram‐per‐Liter Measurements of Hexavalent Chromium in Groundwater - Felix, Allison; Gable, Jennifer; Vitale, Rock; Gratson, David; Carriker, Neil (Environmental toxicology and chemistry, 2020)
The US Environmental Protection Agency (USEPA) and several states are considering regulatory limits for hexavalent chromium (Cr(VI)) <100 ng/L, increasing the importance of obtaining accurate and reliable data. The present study presents the results of 2 studies investigating the effectiveness of chemical preservation on ng/L concentrations of Cr(VI) in groundwater. Chemically preserved and unpreserved aliquots of a groundwater sample were spiked with a known amount of Cr(VI), and then analyzed in tandem with sets of preserved and unpreserved performance test samples over 28 d. The studies showed that although Cr(VI) appears to be relatively stable over 28 d, it may be sensitive to minor matrix changes after collection. The studies also demonstrated significant challenges to measuring Cr(VI) below 100 ng/L, because the results can be subject to positive bias or contamination that may not be readily apparent. We conclude that Cr(VI) measurements using a USEPA published method below 100 ng/L may be categorized as semiquantitative at best. Environ Toxicol Chem 2020;39:1526–1533. © 2020 SETAC